2021
DOI: 10.1186/s41824-021-00102-5
|View full text |Cite
|
Sign up to set email alerts
|

SMARCA4-deficient thoracic tumor detected by [18F]FDG PET/CT

Abstract: Background SMARCA4-deficient thoracic tumor (SMARCA4-DTT) is a distinct entity of undifferentiated thoracic malignancies newly introduced in 2015. Due to its unique clinical characteristic with aggressive thoracic tumor mostly observed in heavy smoker man with emphysema, with poor prognosis, many physicians are becoming increasingly aware of the disease; however, reports on 2-deoxy-2-[18F] fluoroglucose positron emission tomography/computed tomography ([18F]FDG PET/CT) have been limited; thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…First-line median progression-free survival (PFS) was significantly higher for patients with ICI plus chemotherapy than those treated with only chemotherapy [23][24][25] as shown in Table 2. Sauter et al 24 described a case of 69-year-old woman with SMARCA4-dUT who was treated with only chemotherapy and radiotherapy but ultimately succumbed to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…First-line median progression-free survival (PFS) was significantly higher for patients with ICI plus chemotherapy than those treated with only chemotherapy [23][24][25] as shown in Table 2. Sauter et al 24 described a case of 69-year-old woman with SMARCA4-dUT who was treated with only chemotherapy and radiotherapy but ultimately succumbed to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The 18F-FDG-PET/CT demonstrated a strong metabolic activity in both SMARCA4-dNSCLC (SUVmax 13.4 ± 3.2) and SMARCA4-dUT (SUVmax 11.7 ± 6.3) patients, indicating that these tumor types are highly aggressive. For solid mass with high SUVmax value, differential diagnosis should include SMARCA4 de cient tumor, SCLC, NSCLC, lymphoma and non-seminomatous germ cell tumor; thus, surgery should be performed after histological, mediastinal and systemic staging (Okazaki et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…2 A small number of previous studies have reported the use of 18 F-FDG PET/CT in thoracic SMARCA4-UT. 3,4 However, no study has investigated the usefulness of 68 Ga-DOTA-FAPI-04 PET/CT for the evaluation of thoracic SMARCA4-UT. Thoracic SMARCA4-UT is classified as an undifferentiated tumor of pulmonary epithelial origin in the World Health Organization classification.…”
Section: Figurementioning
confidence: 99%
“…It is an aggressive tumor that metastasizes rapidly 2. A small number of previous studies have reported the use of 18 F-FDG PET/CT in thoracic SMARCA4-UT 3,4. However, no study has investigated the usefulness of 68 Ga-DOTA-FAPI-04 PET/CT for the evaluation of thoracic SMARCA4-UT.…”
mentioning
confidence: 99%